INFLUENCE OF CONDITIONS OF ECONOMIC SYSTEMS ON INNOVATION PROCESSES IN MODERN INTERNATIONAL ECONOMIC ENVIRONMENT - Kotane, Inta; Yegorova, Irina; Puriy, Hanna; Hushko, Serhii; Kulishov, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the paper is to analyse the relationship between the state of economic systems and the innovative activity of industrial enterprises in accordance with the peculiarities of the development of national economies in the global economic environment. The general scientific research methods are used in the research study: information analysis and synthesis, logical construction, monographic, data grouping, and graphical display methods. The character of the influence of a stable economic system (on the example of Latvia) and an unstable economic system (on the example of Ukraine) on innovative development is established. The main factors stimulating innovations in different national conditions in the context of modern international trends of innovative development are revealed. The main directions of the impact on innovation processes and the principles of innovation development policy are defined.